PENGARUH PENAMBAHAN BUAH NAGA SEBAGAI PEWARNA ALAMI TERHADAP KARAKTERISTIK FISIKOKIMIA DAN HEDONIK PADA PERMEN JELLY DARI RUMPUT LAUT Kappaphycus alvarezii - Reni, Zepherina; Kusumaningrum, Indrati; Asikin, Andi Noor; Diachanty, Seftylia; Zuraida, Ita (Sam Ratulangi University, 2024)
Jelly candy has a characteristic sweet taste and a chewy texture. Another factor that determines the quality of jelly candy besides the taste and texture is the color. One of the ingredients that has the potential as a natural dye is red dragon fruit which has a sweet taste and is good for increasing endurance. This study aims to determine the addition of dragon fruit as a natural dye to the physicochemical and hedonic characteristics of jelly candy from seaweed Kappaphycus alvarezii. The concentration of dragon fruit juice used is P0: dragon fruit juice 0%, P1: dragon fruit juice 7.5%, P2: dragon fruit juice 10%, P3: dragon fruit juice 12,5%, P4: dragon fruit juice 15%, and P5: dragon fruit juice 17.5%. This study used a completely randomized design for proximate and color tests, and Kruskal-Wallis for hedonic tests. The results showed that the addition of dragon fruit juice had a significant effect (p<0.05) on moisture content, ash content, protein content, fat content, color and hedonic value (color, taste, texture, aroma). The moisture content of the jelly candy ranges from 14.81-22.80%, the ash content ranges from 1.60-3.66% and has met the standard of SNI 3547.2-2008. The brightness value of jelly candy ranges from 12.51-14.06%. The hedonic sensory test (scale 1-5) showed that the jelly candy was well received by the panelists, based on the parameters of color (4.30), taste (3.97), texture (3.97), and aroma (3.77).